America's 100 Most Important Women from Super Stars to Super Inspiring (Ladies' Home Journal)
Who are the most important women in America today? What kind of power and influence do they wield? The women here—chosen by the editors of Ladies' Home Journal—are a fascinating, sometimes surprising group that reflects the multifaceted, still-evolving role of women on the eve of the 1990s.